Management of children with solid organ injuries after blunt torso trauma. Issue 2 (August 2015) - Wisner, David H.; Kuppermann, Nathan; Cooper, Arthur; Menaker, Jay; Ehrlich, Peter; Kooistra, Josh; Mahajan, Prashant; Lee, Lois; Cook, Lawrence J.; Yen, Kenneth; Lillis, Kathy; Holmes, James F.
<x xml:space="preserve">Abstract</x> BACKGROUND Management of children with intra-abdominal solid organ injuries has evolved markedly. We describe the current management of children with intra-abdominal solid organ injuries after blunt trauma in a large multicenter network. METHODS We performed a planned secondary analysis of a prospective, multicenter observational study of children (<18 years) with blunt torso trauma. We included children with spleen, liver, or kidney injuries identified by computed tomography, laparotomy/laparoscopy, or autopsy. Outcomes included disposition and interventions (blood transfusion for intra-abdominal hemorrhage, angiography, laparotomy/laparoscopy). We performed subanalyses of children with isolated injuries. RESULTS A total of 12, 044 children were enrolled; 605 (5.0%) had intra-abdominal solid organ injuries. The mean (SD) age was 10.7 (5.1) years, and injured organs included spleen 299 (49.4%), liver 282 (46.6%), and kidney 147 (24.3%). Intraperitoneal fluid was identified on computed tomography in 461 (76%; 95% confidence interval [CI], 73–80%), and isolated solid organ injuries were present in 418 (69%; 95% CI, 65–73%). Treatment included therapeutic laparotomy in 17 (4.1%), angiographic embolization in 6 (1.4%), and blood transfusion in 46 (11%) patients. Laparotomy rates for isolated injury were 11 (5.4%) of 205 (95% CI, 2.7–9.4%) at non-freestanding children's hospitals and 6 (2.8%) of 213 (95% CI, 1.0–6.0%) at freestanding children's hospitals (difference, 2.6%; 95% CI, −7.1% to 12.2%). Dispositions of the 212 children with isolated Grade I or II organ injuries were home in 6 (3%), emergency department observation in 9 (4%), ward in 114 (54%), intensive care unit in 73 (34%), operating suite in 7 (3%), and transferred in 3 (1%) patients. Intensive care unit admission for isolated Grade I or II injuries varied by center from 9% to 73%. CONCLUSION Most children with solid organ injuries are managed with observation. Blood transfusion, while uncommon, is the most frequent therapeutic intervention; angiographic embolization and laparotomy are uncommon. Emergency department disposition of children with isolated Grade I to II solid organ injuries is highly variable and often differs from published guidelines. LEVEL OF EVIDENCE Prognostic/epidemiologic study, level III; therapeutic study, level IV.